Encyclopedia of child behavior and development - Goldstein, Sam.; Naglieri, Jack A.; SpringerLink (Online service). (New York Springer, 2011)
This major reference work breaks new ground as an electronic resource for students, educators, researchers, and professionals. Encyclopedic in breath, textbook in depth, Child Behavior and Development serves as a reference repository of knowledge in the field as well as a frequently updated conduit of new knowledge long before such information trickles down from research to standard textbooks. Presented in A to Z format, the Encyclopedia of Child Behavior and Development consists of three volumes that address the major conceptual areas of child development: learning, behavior, and emotions. Taking advantage of the techniques offered by the electronic medium, the Encyclopedia of Child Behavior and Development offers an extensive cross-referencing system that facilitates speedy search and retrieval of information.
Electronic reproduction.
Keywords: Child development -- Encyclopedias; Child psychology; Child psychology -- Encyclopedias; Electronic books